Recent HIV-1 infection in a high-risk Ugandan cohort: implications for Phase IIB test-of-concept HIV vaccine trials. (April 2007) - Kebba, Anthony; Imami, Nesrina; Bugembe-Lule, Daniel; Senkaali, David; Kaleebu, Pontiano; Grosskurth, Heiner; Gotch, Frances
Assessment of vaccine efficacy on end points used in Phase IIB test-of-concept trials will require taking into consideration the effect of variables correlated with the end points and distribution of the variables within subgroups of the trial population. Here we report that evaluation of sexual activity in vaccinees and longitudinal collection of plasma viral load data from putative transmitters prior to transmission will contribute to the plausible assessment of efficacy against acquisition of infection. Data also suggest that efficacy on post-infection end points may depend on whether transmission pairs are matched or mismatched for HLA class I alleles.